IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KOTA LAYAK ANAK (KLA) DI KOTA KENDARI - Muhammad Elwan, La Ode (Universitas Halu Oleo, 2019)
ABSTRACTThe purpose of this research is to know the City Development Policy Implementation Worth Children in the town of Kendari. The location of the research is on Duty and authorized Agencies in the task force as well as Decent City Development Forum of the child, the child's caregivers and the business world in the city of Kendari. This type of research is a Qualitative Description. Informants in this study a total of 11 people which is the representation of the regional development planning board, a body of women empowerment and child protection, Education, health services, Social Service, Department of labor, Police Resort Kendari, the children's Forum, the task force of the sub district, and recipient of the City Program Worth Child Kendari. The technique of data collection in this research is the observation, interview and study documents. The analysis of the data used in this research in the form of data collection, reduction of: 1) maximize the synchronization with equating views on the urgency of the fulfillment of children's rights for work unit area devices; 2) implement the coordination between the task force as well as Decent Town monitoring at regular intervals and follow-up; 3) Effective use of guesthouses by the Government so that local government Kendari can provide guidance and rehabilitation for street children; 4) Socialization and strengthening child protection task force levels of the tenets of citizenship as a whole in preventing acts of violence, as well as roles and functions, can be recognized by the public. Keywords: Implementation Policy, The City Deserves A Child